PENGARUH ANTESEDEN KEPUASAN DALAM MENINGKATKAN LOYALITAS KONSUMEN - Teguh Setiadi; Tulus Haryono (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2016)
The purpose of this study was to examine the effect of personal interaction quality between employer with their customer, relationship quality between employer with their customer, product and service quality on customer loyalty PT. Asuransi Jasindo Solo Branch Office with customer satisfaction as a mediating variable. Collecting data using a questionnaire. The population of this study are all customers of PT. Asuransi Jasindo Solo Branch Office using existing in Surakarta. The sampling technique using purposive sampling technique, with a sample of 200 people. Analysis using structural equation model (Structural Equation Modeling / SEM), with the additional of AMOS programme. The results showed: Personal interaction quality has a positive and significant impact on relationship quality with the customer. Relationship quality has a positive and significant impact on customer satisfaction. Relationship quality has a positive and significant impact on customer loyalty. Product quality has a positive and significant impact on customer satisfaction. Service quality has a positive and significant impact on customer satisfaction. Service quality has no effect on customer loyalty. Customer satisfaction has a positive and significant impact on customer loyalty PT. Asuransi Jasindo in Solo.